Mechanical Properties, Corrosion Behavior, and In Vitro Cell Studies of the New Ti-25Ta-25Nb-5Sn Alloy - Silva, Kerolene Barboza da [UNESP]; Carobolante, João Pedro Aquiles [UNESP]; Rajan, S. Sudhagara [UNESP]; Júnior, Celso Bortolini [UNESP]; Sabino, Roberta Maia; Seixas, Maurício Rangel [UNESP]; Nakazato, Roberto Zenhei [UNESP]; Popat, Ketul C.; Claro, Ana Paula Rosifini Alves [UNESP] (MDPI, 2023)
This study aims to characterize a new Ti-25Ta-25Nb-5Sn alloy for biomedical application. Microstructure, phase formation, mechanical and corrosion properties, along with the cell culture study of the Ti-25Ta-25Nb alloy with Sn content 5 mass% are presented in this article. The experimental alloy was processed in an arc melting furnace, cold worked, and heat treated. For characterization, optical microscopy, X-ray diffraction, microhardness, and Young’s modulus measurements were employed. Corrosion behavior was also evaluated using open-circuit potential (OCP) and potentiodynamic polarization. In vitro studies with human ADSCs were performed to investigate cell viability, adhesion, proliferation, and differentiation. Comparison among the mechanical properties observed in other metal alloy systems, including CP Ti, Ti-25Ta-25Nb, and Ti-25Ta-25-Nb-3Sn showed an increase in microhardness and a decrease in the Young’s modulus when compared to CP Ti. The potentiodynamic polarization tests indicated that the corrosion resistance of the Ti-25Ta-25Nb-5Sn alloy was similar to CP Ti and the experiments in vitro demonstrated great interactions between the alloy surface and cells in terms of adhesion, proliferation, and differentiation. Therefore, this alloy presents potential for biomedical applications with properties required for good performance.
Keywords: biomaterials; cell culture; corrosion behavior; mechanical properties; Ti-Ta-Nb-Sn